Homegrown Views? Exploring Immigrant and Racialized People’s Perceptions of Police in Canada - Jung, Maria (Canadian journal of criminology and criminal justice, 2021)
When compared to studies examining racialized people’s perceptions of police in North America, studies of immigrants’ views of police are quite rare and they often conflate the views of immigrants with those of racialized people. Yet, we know racialized people are not necessarily immigrants and immigrants are not necessarily racialized. Research that distinguishes immigrant status from racialized status has found important differences based on immigrant vs. native-born status, country of origin, and length of settlement. This research builds on these findings by specifically considering the relative influence of universal and immigrant-specific factors that may shape within-group views of police. Using the 2014 General Social Survey, variations in views of police among South Asians - Canada’s largest racialized group - are explored by whether they were born in Canada, immigrated recently, or had long settled within Canada. Our findings suggest that traditional measures - or the universal factors - used to assess perceptions of police may not explain immigrants’ views in the same way that they do for native-born individuals, and that immigrants’ views of police may be shaped in ways that are, as of yet, unaccounted for in the literature.